Wilms' tumor 1 -targeting cancer vaccine: Recent advancements and future perspectives - Masahiro Ogasawara (Taylor & Francis Group, 2024)
ABSTRACTThis mini-review explores recent advancements in cancer vaccines that target Wilms' tumor (WT1). Phase I/II trials of WT1 peptide vaccines have demonstrated their safety and efficacy against various cancers. Early trials employing HLA class I peptides evolved through their combination with HLA class II peptides, resulting in improved clinical outcomes. Additionally, WT1-targeted dendritic cell vaccines have exhibited favorable results. Studies focusing on hematological malignancies have revealed promising outcomes, including long-term remission and extended survival times. The combination of vaccines with immune checkpoint inhibitors has shown synergistic effects. Current preclinical developments are focused on enhancing the effectiveness of WT1 vaccines, underscoring the necessity for future large-scale Phase III trials to further elucidate their efficacy.